Die Literaturen Südosteuropas, 15. bis frühes 20. Jahrhundert Ein Vergleich - Puchner, Walter (2015)
This book is the basis of comparative literature studies of Southeast-Europe from the late medieval period to early 20th century in the near future and compare for the first time the development of genres and periods of fiction, ideological tendencies, themes and motives, reception and influences concerning the literatures of Hungary and Rumania, the South Slavic countries, Albania, Greece and Turkey.